Exporting Culture: a Requirement for Competitive Internationalization* (2005)
his paper proposes a concept of “culture for internationalization” and “exporting culture” –a highly relevant concept for developing countries’ firms that are likely to follow a gradualinternationalization process– based on the strong relationship binding the concept proposed to strategy and systemic competitiveness. These three items are paramount to Understand the conditions underlying internationalizationas it is characterized by particular traits that make it a key alternative for a firm’s growth and successful perdurability based on competitiveness. “Culture for internationalization” and its variation, “exporting culture”, overflow the conceptsof organizational or corporate culture and involve some major interaction among the micro, meso and macro levels of a national economy in order to operationalize strategies thatpromote such culture and assure successful firm and economy internationalization. Discussion remains open as to the concept and its applicability with the hope that it contributesto the understanding and creation of appropriate conditions for firms to be able to access international markets with greater advantage and generate as much benefit as possible totheir nations, particularly in developing countries.